The non-prototypical discourse marker zdaj - Majhenič, Simona; Rojc, Matej; Mlakar, Izidor (Slavia Centralis, 2022)
The present paper presents a qualitative case study of the Slovene discourse marker zdaj (now), which, thus far, has been explored in its prosodically prominent structure or as a prototypical discourse marker. The structural, i.e., the prosodical analysis, highlights that the discourse marker zdaj also manifests in its non-prototypical form. By means of semantic analysis, underpinned by paraphrase and translation tests, we suggest that the non-prototypical form signals subtler frame shifts than its prototypical counterpart, and that it primarily functions as an emphasis device, whereas the prototypical zdaj predominately performs discourse structuring functions.
Keywords: discourse markers; (non-)prototypical markers; prosody; Praat; translation test; spoken language